Activation of cyclin A-dependent protein kinases during apoptosis. - Meikrantz, W (1994)
Apoptosis was induced in S-phase-arrested HeLa cells by staurosporine, caffeine, 6-dimethylaminopurine, and okadaic acid, agents that activate M-phase-promoting factor and induce premature mitosis in similarly treated hamster cell lines. Addition of these agents to asynchronously growing HeLa cells or to cells arrested in early G1 phase with lovastatin had little or no effect. S-phase arrest also promoted tumor necrosis factor alpha-induced apoptosis, eliminating the normal requirement for simultaneous cycloheximide treatment. For all of the apoptosis-inducing agents tested, the appearance of condensed chromatin was accompanied by 2- to 7-fold increases in cyclin A-associated histone H1 kinase activity, levels approximating the mitotic value. Where examined, both Cdc2 and Cdk2, the catalytic subunits known to associate with cyclin A, were activated. Stable overexpression of bcl-2 suppressed the apoptosis-inducing activity of all agents tested and reduced the amount of Cdc2 and Cdk2 in the nucleus, suggesting a possible mechanism by which bcl-2 inhibits the chromatin condensation characteristic of apoptosis. These findings suggest that at least one of the biochemical steps required for mitosis, activation of cyclin A-dependent protein kinases, is also an important event during apoptosis.